1993
DOI: 10.1128/aac.37.9.1896
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the chromosomal aac(6')-Ii gene specific for Enterococcus faecium

Abstract: Chromosomal gene aac(6')-Ii of Enterococcus faecium CIP 54-32, encoding a 6'-N-aminoglycoside acetyltransferase was characterized. The gene was identified as a coding sequence of 549 bp corresponding to a protein with a calculated mass of 20,666 Da. Analysis of the sequence of the deduced protein suggested that it was the second member of a subfamily of AAC(6')-I enzymes. Insertional inactivation of aac(6')-Ii led to aminoglycoside susceptibility of CIP 54-32, suggesting that this gene plays a role in resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
117
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(120 citation statements)
references
References 36 publications
1
117
0
2
Order By: Relevance
“…The BLAST results contain mostly GCN5-related N-acetyltransferases (GNAT) from different bacteria, with the top hit being an uncharacterized protein from Enterococcus faecium strain DO; therefore, we named this unknown gene YJM-GNAT. Some members of the GNAT superfamily are known to confer resistance to aminoglycoside antibiotics in certain bacteria, such as E. faecium (31,32) and Salmonella enterica (33). Furthermore, the phylogeny for YJM-GNAT differs dramatically from phylogenies obtained for other YJM789 genes (see Fig.…”
Section: Resultsmentioning
confidence: 91%
“…The BLAST results contain mostly GCN5-related N-acetyltransferases (GNAT) from different bacteria, with the top hit being an uncharacterized protein from Enterococcus faecium strain DO; therefore, we named this unknown gene YJM-GNAT. Some members of the GNAT superfamily are known to confer resistance to aminoglycoside antibiotics in certain bacteria, such as E. faecium (31,32) and Salmonella enterica (33). Furthermore, the phylogeny for YJM-GNAT differs dramatically from phylogenies obtained for other YJM789 genes (see Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Integrons could "mop" up these genes following excision, and incorporate them into replicons, which could then be transferred among bacterial pathogens. Several pieces of evidence similarly support the hypothesis that housekeeping genes have evolved to modify antibiotics and that their recruitment could provide an alternate source of resistance genes [23,68]. All resistance-encoding DNAs establish a resistance gene pool, which represents a potential source of gene cassettes incorporated into the integrons [28].…”
Section: Mobile Gene Cassettesmentioning
confidence: 92%
“…• the chromosomal gene aac(6')-Ii, which encodes for a 6´-N-aminoglycoside acetyltransferase (Moellering et al, 1979;Costa et al 1993). Regarding the comment on amikacin resistance, raised in paragraph 7, it is reported that aac(6')-Ii does not confer high-level resistance to amikacin in E. faecium (Moellering, 1979).…”
Section: Intrinsic Resistancementioning
confidence: 99%
“…Regarding the comment on amikacin resistance, raised in paragraph 7, it is reported that aac(6')-Ii does not confer high-level resistance to amikacin in E. faecium (Moellering, 1979). A linkage between this gene and amikacin resistance has been observed only in E. coli when aac(6')-Ii is over-expressed, being harboured by a multicopy plasmid (Costa et al, 1993); and…”
Section: Intrinsic Resistancementioning
confidence: 99%